Inhibitory Effect of Long-Chain Fatty Acids on Biogas Production and the Protective Effect of Membrane Bioreactor. (8th September 2016) - Dasa, Kris Triwulan; Westman, Supansa Y.; Millati, Ria; Cahyanto, Muhammad Nur; Taherzadeh, Mohammad J.; Niklasson, Claes
Abstract : Anaerobic digestion of lipid-containing wastes for biogas production is often hampered by the inhibitory effect of long-chain fatty acids (LCFAs). In this study, the inhibitory effects of LCFAs (palmitic, stearic, and oleic acid) on biogas production as well as the protective effect of a membrane bioreactor (MBR) against LCFAs were examined in thermophilic batch digesters. The results showed that palmitic and oleic acid with concentrations of 3.0 and 4.5 g/L resulted in >50% inhibition on the biogas production, while stearic acid had an even stronger inhibitory effect. The encased cells in the MBR system were able to perform better in the presence of LCFAs. This system exhibited a significantly lower percentage of inhibition than the free cell system, not reaching over 50% at any LCFA concentration tested.